Peranan Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak Terhadap Perlindungan Hukum Bagi Anak Jalanan (Qawanin Jurnal Ilmu Hukum, 2021)
AbstractThe purpose of this study was to determine and analyze the role of the integrated service center for the  empowerment of women and children (P2TP2A) on legal protection for street children in the city of Makassar. Research methods The empirical research used shows that the role of the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) on legal protection for street children in Makassar City is to provide legal assistance, provide a place for guidance, safe houses, and strive to return street children so they want to return. go to school by approaching these street children. In addition, the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) also plays an important role in handling children in conflict with the law. The obstacle faced in the role of the Integrated Service Center for the Empowerment of Women and Children (PT2TP2A) on legal protectionfor street children in Makassar City is the lack of socialization to the community so that there are many negative responses from the community to forms of legal protection such as legal assistance to street children who commit criminal acts. , and there is no understanding for the mediation of victims of criminal acts when they meet street children as perpetrators of criminal acts so that they want to be given tribute before carrying out mediation efforts.AbstrakTujuan Penelitian ini untuk mengetahui dan menganalisis peranan pusat pelayanan terpadu pemberdayaan perempuan dan anak (P2TP2A) terhadap perlindungan hukum bagi anak jalanan di kota Makassar. Metode penelitian yang digunakan adalah penelitian empiris hasil penelitian menunjukan bahwa bahwa Peranan Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) terhadap perlindungan hukum bagi anak jalanan di Kota Makassar adalah menyediakan pendampingan hukum, menyediakan tempat pembinaan ,rumah aman, berupaya untuk mengembalikan anak jalanan agar ingin kembali bersekolah dengan cara melakukan pendekatan dengan anak- anak jalanan tersebut. Selain itu Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) juga berperan penting dalam penanganan anak berkonflik dengan hukum. Kendala yang dihadapi dalam peranan Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (PT2TP2A) terhadap perlindungan hukum bagi anak jalanan di Kota Makassar adalah kurangnya sosialisasi kepada masyarakat sehingga banyak tanggapan-tanggapan negatif masyarakat terhadap bentuk perlindungan hukum seperti pendampingan hukum kepada anak jalanan yang melakukan tindak pidana, dan tidak adanya pengertian untuk mediasi dari korban tindak pidana ketika bertemu dengan anak jalanan sebagai pelaku tindak pidana sehingga ingin diberikan upeti sebelum melakukan upaya mediasi.